Elective orthopaedic surgery with a designated COVID-19- free pathway results in low perioperative viral transmission rates. (September 2020) - Chang, . S.; Wignadasan, W.; Pradhan, R.; Kontoghiorghe, C.; Kayani, B.; Haddad, F. S.
No abstract available